ERCC1 and XRCC1 as biomarkers for lung and head and neck cancer - Vaezi A; Feldman CH; Niedernhofer LJ (Dove Medical Press, 2011)
Alec Vaezi1,2, Chelsea H Feldman2, Laura J Niedernhofer2,31Department of Otolaryngology and Head and Neck Surgery, University of Pittsburgh School of Medicine, 2University of Pittsburgh Cancer Institute, 3Department of Microbiology and Molecular Genetics, University of Pittsburgh School of Medicine and Cancer Institute, Pittsburgh, PA, USAAbstract: Advanced stage non-small cell lung cancer and head and neck squamous cell carcinoma are both treated with DNA damaging agents including platinum-based compounds and radiation therapy. However, at least one quarter of all tumors are resistant or refractory to these genotoxic agents. Yet the agents are extremely toxic, leading to undesirable side effects with potentially no benefit. Alternative therapies exist, but currently there are no tools to predict whether the first-line genotoxic agents will work in any given patient. To maximize therapeutic success and limit unnecessary toxicity, emerging clinical trials aim to inform personalized treatments tailored to the biology of individual tumors. Worldwide, significant resources have been invested in identifying biomarkers for guiding the treatment of lung and head and neck cancer. DNA repair proteins of the nucleotide excision repair pathway (ERCC1) and of the base excision repair pathway (XRCC1), which are instrumental in clearing DNA damage caused by platinum drugs and radiation, have been extensively studied as potential biomarkers of clinical outcomes in lung and head and neck cancers. The results are complex and contradictory. Here we summarize the current status of single nucleotide polymorphisms, mRNA, and protein expression of ERCC1 and XRCC1 in relation to cancer risk and patient outcomes.Keywords: nucleotide excision repair, base excision repair, DNA damage, DNA repair, chemotherapy, NSCLC, HNSCC, single nucleotide polymorphism